Understanding peroral absorption: regulatory aspects and contemporary approaches to tackling solubility and permeability hurdles - B. Shekhawat, Prachi (Acta Pharm Sin B, 2017)
Oral drug absorption is a process influenced by the physicochemical and biopharmaceutical properties of the drug and its inter-relationship with the gastrointestinal tract. Drug solubility, dissolution and permeability across intestinal barrier are the key parameters controlling absorption. This review provides an overview of the factors that affect drug absorption and the classification of a drug on the basis of solubility and permeability. The biopharmaceutical classification system (BCS) was introduced in early 90׳s and is a regulatory tool used to predict bioavailability problems associated with a new entity, thereby helping in the development of a drug product. Strategies to combat solubility and permeability issues are also discussed.